Ganano Gateway an eco-corridor design for Baguio Village in Quirino Province aimed towards Protection from Tourism Threats and Enhancement of the Landscape - Gonzalez, Katrina Beatriz M.
As societies and cities continue to evolve, people have become more and more distanced from nature. Living in urban areas has shown to develop a greater need or desire to be closer to nature. This need or desire sparked the continuous growth of tourism through the decades and although tourism provides many benefits to man, it also poses many negative impacts to the environment and local communities involved. In the case of Baguio Village, the barangay is located along the Ganano Watershed and serves as the only access point the Ganano Waterfalls – a tourist site growing in popularity. The local community is now slowly exhibiting the negative impacts of tourism such as littering, influx of tourists and degradation of the landscape. This research aims to develop an Eco-Corridor that can protect the environment and local community from these emerging threats and also enhance the landscape. Furthermore, the study aims to show that eco-corridor design can be used as an effective design intervention in protecting and enhancing the landscape in a way that benefits the environment, the local community and the tourists.